THE RELATIONSHIP BETWEEN ACADEMIC STRESS LEVELS AND ONLINE GAME ADDICTION TENDENCIES AMONG STUDENTS OF SMK MUHAMMADIYAH 1 TAMAN - Choirina , Faizah Nur; Ghozali Rusyid Affandi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to identify and analyze the relationship between academic stress level and online game addiction tendency among students at SMK Muhammadiyah 1 Taman. In the digital era, online gaming has become a popular phenomenon among students, but it also has the potential to cause addiction that can have a negative impact on academic aspects and mental health. Method: The method used in this study was a quantitative non-experiment involving 182 students randomly drawn from the population of SMK Muhammadiyah 1 Taman. Data were collected using a Likert scale designed to measure academic stress levels and online game addiction tendencies. Results: The results of the analysis using the Spearman correlation test showed a positive and significant relationship between academic stress level and online game addiction tendency, with a correlation coefficient of 0.161 and a significance value of p = 0.030. This finding indicates that the higher the level of academic stress experienced by students, the greater their tendency to experience addiction to online games. Novelty: This study provides important insights for educational institutions to develop interventions that can assist students in managing stress and preventing addictive behaviors. Implications of the results include the need for preventive approaches in education to support students' mental health, including counseling services and stress management training. By understanding this relationship, it is expected to reduce the negative impact of academic stress on addictive behaviors among students.